Safety, Pharmacokinetics and Pharmacodynamics of the Selective Glucocorticoid Receptor Modulator Velsecorat (AZD7594) Following Inhalation in Healthy Volunteers - Prothon S; Aurivillius M; Tehler U; Eriksson UG; Aggarwal A; Chen Y (Dove Medical Press, 2022)
Susanne Prothon,1 Magnus Aurivillius,2 Ulrika Tehler,3 Ulf G Eriksson,1 Ajay Aggarwal,4 Yingxue Chen5 1Clinical Pharmacology and Quantitative Pharmacology, Clinical Pharmacology & Safety Sciences, R&D, AstraZeneca, Gothenburg, Sweden; 2Late Stage Development, Respiratory & Immunology, BioPharmaceuticals R&D, AstraZeneca, Gothenburg, Sweden; 3Advanced Drug Delivery, Pharmaceutical Sciences, R&D, AstraZeneca, Gothenburg, Sweden; 4Research and Early Development, Respiratory & Immunology, BioPharmaceuticals R&D, AstraZeneca, Boston, MA, USA; 5Clinical Pharmacology and Quantitative Pharmacology, Clinical Pharmacology and Safety Sciences, R&D, AstraZeneca, Boston, MA, USACorrespondence: Susanne Prothon, Clinical Pharmacology and Quantitative Pharmacology, Clinical Pharmacology & Safety Sciences, R&D, AstraZeneca, Pepparedsleden 1, Mölndal, Gothenburg, 431 83, Sweden, Email susanne.prothon@astrazeneca.comIntroduction: Velsecorat (AZD7594) is a non-steroidal, selective, glucocorticoid receptor modulator (SGRM), being developed for the treatment of asthma. This article reports the initial, first-in-human, single and repeat dose-escalating study in healthy male volunteers.Methods: The study comprised two parts, a single ascending dose part (n=47) and a multiple ascending dose part (n=26). Inhaled velsecorat was administered by nebulization as one single dose in the first part of the study and as a single dose with subsequent multiple daily doses (day 5- 16) for 12 days once daily in the second part of the study. At each dose level, participants were randomized to velsecorat (n=6) or placebo (n=2/3). The safety, pharmacokinetics (PK) and pharmacodynamics (PD) of velsecorat were evaluated.Results: Inhaled velsecorat was safe and well tolerated up to and including the highest dose tested (1872 μg). Plasma exposure suggested dose proportional PK. The terminal half-life following repeated dosing was 25- 31 hours and steady state conditions for velsecorat in plasma were generally reached within 4 doses. The accumulation ratio was low (≤ 2), and data did not indicate any time-dependent PK. There were dose-related effects on 24-hour plasma cortisol, plasma cortisol after ACTH stimulation and osteocalcin, systemic PD markers of glucocorticoid activity. There were no effects on other biomarkers tested (DHEA-S and 4βOH-cholesterol).Conclusion: The early clinical evaluation of inhaled velsecorat suggests that this novel SGRM is well tolerated in the dose range investigated. It shows dose proportional plasma exposure, low accumulation, and has dose-dependent effects on markers of glucocorticoid activity.Keywords: AZD7594, velsecorat, pharmacokinetics, non-steroidal glucocorticoid receptor modulator, PK